Otonomi Daerah dan Demokratisasi di Indonesia Ditinjau Dari Undang-Undang Otonomi Daerah - Simbolon, Lamtio Oktafiana BR; Ananta, Assyifa Futri; Rizqa, Nabila Wanda; Rahmayani, Elsa Sely (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This research discusses community participation in building regional autonomy in Indonesia. With the passing of Law No. 22 of 1999 on Regional Autonomy, the democratization process of establishing regional autonomy began. Regional autonomy is defined as the right, authority, and obligation of autonomous regions to regulate and manage their own households. However, community participation in decision-making is often misinterpreted as simply agreeing with decisions that have been made by the government bureaucracy, so it is not directly involved in decision-making. This research also discusses the local government bureaucratic system and how community participation can improve the quality of local government. Community participation is seen as an active process where people take initiatives and actions stimulated by their own thoughts and decisions. Therefore, community participation is more than just an instrument to implement government projects. This research shows that community participation is important in sustainable development strategies and can enable the mobilization of local knowledge and resources for self-reliant development. However, the problems of community participation in each region still occur, such as not having an effective dialog mechanism and space for community involvement in decision-making.